2018
DOI: 10.1007/s10725-018-0428-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of co-inoculation of two different plant growth-promoting bacteria on duckweed

Abstract: Aseptic Lemna minor was soaked for 4 h in pond water where wild L. minor was naturally flourishing. Seven of the eight surface-colonizing bacterial strains were found capable of promoting the growth of L. minor. This high appearance of plant growth-promoting bacteria (PGPB) suggests that association of environmental bacteria is generally beneficial rather than harmful for host plants. One of the PGPB, Pseudomonas sp. Ps6, enhanced the growth of L. minor by 2-2.5-fold in 10 days. This activity was higher than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…In summary, our work increases our understanding of the mechanics of complex and multifactorial bacterial social interactions, demonstrating that the strategies adopted by two bacterial species may co-exist and lead to the formation of stable bacterial communities in plants, either mixed or as physically separated sub-domains. The findings obtained could be potentially relevant for agricultural purposes as shown by other studies 65,66 where the application of bacterial consortia has demonstrated promising effects in plant growth and biocontrol.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In summary, our work increases our understanding of the mechanics of complex and multifactorial bacterial social interactions, demonstrating that the strategies adopted by two bacterial species may co-exist and lead to the formation of stable bacterial communities in plants, either mixed or as physically separated sub-domains. The findings obtained could be potentially relevant for agricultural purposes as shown by other studies 65,66 where the application of bacterial consortia has demonstrated promising effects in plant growth and biocontrol.…”
Section: Discussionsupporting
confidence: 54%
“…Raw reads were quality-trimmed with cutadapt. Then, trimmed reads were mapped against P. chlororaphis PCL1606, B. subtilis 3610 reference genomes using EDGE-pro 65 software, which is specially designed to process prokaryotic RNA-Seq data. Quantification was also performed with EDGE-pro.…”
Section: Methodsmentioning
confidence: 99%
“…Ps6, another PGPB strain, frequently adheres to and colonizes on the root of duckweed ( L. minor ). It enhances the growth of L. minor by 2‐ to 2.5‐fold in 10 days, displaying a much higher activity than that of A. calcoaceticus P23 (Yamakawa, Jog, & Morikawa, 2018). The growth of duckweed rhizosphere‐associated bacteria is dependent on the quality of water.…”
Section: Duckweed In Remediation Of Water Pollutionmentioning
confidence: 99%
“…Acinetobacter calcoaceticus strain P23, which was the first plant growth-promoting bacterial strain isolated from the whole body of Lemna aoukikusa, almost doubled the biomass productivity of this duckweed species 14), 16) . To date, over 15 strains of PGPB belonging to the genera, such as Pseudomonas, Acinetobacter, Sphingomonas, Azospirillum, and Aeromonas have been isolated from duckweed roots or whole plant bodies 14), 15), 17) . However, to the best of our knowledge, PGPB have never been isolated from the fronds of duckweeds.…”
Section: Introductionmentioning
confidence: 99%